Komunikasi Politik Korporat Manchester United: Posisi Klub terhadap Isu-Isu Sosial, Rasisme, dan LGBTQ+ dalam Sepak Bola Modern - M. Ferdi Septianda (Jurnalika : Jurnal Ilmu Komunikasi, 2026)
This study analyzes the corporate political communication strategy of Manchester United in responding to contemporary social issues, specifically racism and LGBTQ+ rights. Using a qualitative approach with library research methods, this research examines how the club communicates its political positions through various platforms, manages conflicts of interest among diverse global stakeholders, and builds its image as a socially responsible organization. The findings reveal that Manchester United demonstrates a more consistent communication pattern on anti-racism issues through the "All Red All Equal" and "See Red" campaigns, supported by strategic partnerships with human rights organizations. However, the club faces significant challenges regarding LGBTQ+ issues, as evidenced by the cancellation of pride-themed jackets in December 2024 following player resistance. The communication strategy employed reflects compromise efforts by prioritizing individual freedom of belief while maintaining verbal commitment to inclusion. This research contributes to organizational communication and political communication literature in sports by demonstrating that global football clubs face structural complexity in managing corporate political communication when confronted with conflicting stakeholder expectations. The effectiveness of Manchester United's political communication varies depending on the level of social consensus on specific issues, with anti-racism campaigns achieving broader legitimacy compared to LGBTQ+ advocacy.